Conceptualizing Urban Economic Resilience at the Time of Covid-19 and Beyond - Pozhidaev, Dmitry (Journal of Applied Business and Economics, 2021)
Economic resilience has been identified as the key factor that defines the ability of urban communities to cope with the consequences of the ongoing COVID-19 crisis as well as any other global health-related economic shocks. This paper offers a dynamic action-oriented concept of urban economic resilience defined as the capacity and related capabilities of urban communities to plan for, anticipate negative shocks, including long-term stresses, to their economies, reallocate and mobilize resources to withstand those shocks, recover from the shocks, and rebuild at least to pre-crisis levels as soon as possible, while placing their economies on the path to sustainable economic growth and simultaneously strengthening their capacity to deal with any future shocks. the paper suggests key operational indicators for the identified variables and discusses how the conceptual framework presented in the paper can be used to measure urban economic resilience and assess city performances.